A mind stretched: The psychology of repeat consumption. Issue 1 (29th November 2020) - O'Brien, Ed
Abstract: Repeat consumption refers to re‐experiencing an enjoyable stimulus in order to enjoy it again. We rewatch the same shows, reread the same stories, and revisit the same cities; we play our favorite songs on loop and stick to our secret spots in town. When and why do people engage in repeat consumption, and what actually happens in our psychological experience (e.g., attention, enjoyment) upon doing so? This article reviews burgeoning research shedding light on these questions. First, I establish repeat consumption as a distinct construct. Second, I highlight an emerging perspective: Repeat consumption is not so repetitive after all. Not only does repetition reveal new things within the stimulus—dubbed stimulus‐level novelty (e.g., upon rewatching a movie, we notice missed details and new connections)—but we also learn new things about ourselves in the process—dubbed self‐level novelty (e.g., "I must really be committed!"). This model qualifies traditionally grim understandings of hedonic adaptation and exposure effects; people derive greater utility from the old and familiar than assumed. Third, I highlight future research directions, including the need for a clearer taxonomy of repeat value and implications for maximizing utility. Exciting discoveries lie ahead if we return to where we have already been.